The 2024 Presidential Election's Political Dynamics: The Changing of Governments and Dynasties - Akbar, Yonarisman Muhammad; Windyaningrum, Rachmawati; Rosadi, Raesita Rakhmawati; Fiani, Isma Dwi; Fajrini, Nurkhalila (Ilomata International Journal of Social Science, 2024)
This article examines the political dynamics taking place during the presidential election of Indonesia in 2024, with a focus on the transition to a new government and the potential emergence of political dynasties. It analyzes the political changes that occurred during the campaign, election, and post-election, and how these changes affected political stability and the country's policy direction. Changes in public opinion, political communication tactics used by candidates and political parties, difficulties encountered during the transition to a new government, and the potential emergence of political dynasties—a phenomenon in which political power is concentrated in the hands of families or power circles—are all included in the analysis. The research method used is qualitative research with a literature study design. The data collection technique uses secondary data from reference sources such as legal products, research articles, and journals collected from Google Scholar, Portal Garuda, and news portals such as BBC Indonesia, BBC News, Kompas.com, and Bawaslu. The literature study technique uses a traditional review. This article seeks to offer a clearer understanding of the political processes influencing the 2024 presidential election result and its consequences for Indonesia's political future by exploring these dynamics.